Synergy of the Community and the Police in Realizing Environmental Security in Sumber Jaya Village, Jati Agung District, South Lampung, Siyāsah Tanfīdziyyah Perspective - Rhiska Novita Sari; Agustina Nurhayati; Li’izza Diana Manzil (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2026)
This study aims to analyze the synergy between the community and the police in ensuring neighborhood security in Sumber Jaya Village, Jati Agung Subdistrict, South Lampung Regency, and to examine it from the perspective of Siyāsah Tanfīdziyyah. This study employs a field research method with a descriptive qualitative approach. Primary data was collected through interviews with neighborhood watch officers, community members, community leaders, and police officials, while secondary data was obtained from relevant laws and regulations, books, journals, and scientific literature. Data collection techniques involved interviews and documentation, followed by qualitative descriptive analysis. The results indicate that the synergy between the community and the police in Sumber Jaya Village has functioned effectively through the Neighborhood Watch (Siskamling) program, night patrols, and community outreach and patrols conducted by the police. This collaboration reflects active community participation and the police's fulfillment of security functions in maintaining environmental order. 1 This synergy enhances the community's sense of security and helps reduce the potential for criminal activity in the village. However, the implementation of environmental security still faces several challenges, such as low discipline among some patrol officers, weather conditions, and the suboptimal use of modern security technology. From the perspective of executive governance, the synergy between the community and the police reflects the government's executive functions in the realm of public security and order. As the implementers of state policy, police officers bear the responsibility of maintaining social stability and providing protection to the community, while the community serves as a partner supporting the creation of community security through active participation in Siskamling activities.